REPRESENTASI HUMOR SARKASME PADA VIDEO YOUTUBE UNCLE ROGER - Fella Rahmah Putri; Ida Ri'aeni; Ririn Risnawati (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2022)
A comedian has a function to entertain the audience. He displays interesting content and can lead the audience to laugh. Humor put forward by comedians consists of aspects of verbal actions carried out by speakers which we usually call aspects of the mouth and nonverbal aspects, namely with other body movements which are stimulating, cognitive and intellectual activities as assessment and evaluation as well as those that are visible from smiles and laughter. . It is interesting to study with semiotic method. Semiotics is the science or method of analysis to study signs. Semiotics has various types, one of which is Social Semiotics. This research is about sarcasm humor in Uncle Roger's Youtube video content entitled